2023
DOI: 10.1002/gj.4824
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical characteristics and genetic types of crude oils from a variety of geological reservoir rocks (Cretaceous–Palaeogene) in the Melut Basin, southern Sudan based on biomarker and carbon isotope composition

Mohammed H. Hakimi,
Atif N. Abass,
Afikah Rahim
et al.

Abstract: This study uses physical and geochemical characteristics of crude oil samples representing the Cretaceous and Palaeogene reservoir sequence of the Melut Basin, southern Sudan to gain information about source rock properties, including organic matter characters, depositional environment and thermal maturity. The overall results show that the Melut Basin's oils have API values between 14.6° and 33.3° and indicate that most of oils are not biodegraded; except one heavy oil sample with low API gravity of 14.6°, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
(100 reference statements)
0
2
0
Order By: Relevance
“…Hakimi, Abass, et al (2023) studied the physical and geochemical characteristics of crude oil samples representing the Cretaceous and Palaeogene reservoir sequences of the Melut Basin, southern Sudan, to gain information about source rock properties, including organic matter characters, depositional environment and thermal maturity. According to the biomarker maturity indicators, they revealed that most of the Melut Basin's oils were generated in the main stage of oil generation, exhibiting a range of peak mature to late mature.…”
Section: Petroleum Geochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Hakimi, Abass, et al (2023) studied the physical and geochemical characteristics of crude oil samples representing the Cretaceous and Palaeogene reservoir sequences of the Melut Basin, southern Sudan, to gain information about source rock properties, including organic matter characters, depositional environment and thermal maturity. According to the biomarker maturity indicators, they revealed that most of the Melut Basin's oils were generated in the main stage of oil generation, exhibiting a range of peak mature to late mature.…”
Section: Petroleum Geochemistrymentioning
confidence: 99%
“…and elsewhere in similar depositional settings Kumar et al (2023a). use high-quality three-dimensional (3D) seismic reflection data to decipher the fluid contact zones and their types from the well-known Tipam reservoir in the petroliferous Upper Assam foreland basin; thus, potential clues to favourable reservoir types have been obtained.3 | PETROLEUM GEOCHEMISTRYHakimi, Abass, et al (2023) studied the physical and geochemical characteristics of crude oil samples representing the Cretaceous and Palaeogene reservoir sequences of the Melut Basin, southern Sudan, to gain information about source rock properties, including organic matter characters, depositional environment and thermal maturity.According to the biomarker maturity indicators, they revealed that most of the Melut Basin's oils were generated in the main stage of oil generation, exhibiting a range of peak mature to late mature. The biomarker environmental indicators reveal that the shale source rocks of the Al-Gayger and Galhak formations contributed to these oil samples.On the other hand,Hakimi, Alaug, et al (2023) examined organic-rich shale samples of the Late Cretaceous Mukalla Formation using bulk organic geochemistry, microscopic examination and biomarker measurements combined with 1-D basin modelling to evaluate the organic matter characteristics and their ability to generate gas.…”
mentioning
confidence: 99%